Evaluation of a research training workshop for academic staff in tertiary institutions: A Kirkpatrick model approach (Journal of Applied Learning and Teaching, 2024)
Quality research has a positive impact on the development of a country. Literature has shown that there is a limited quantity of quality African research articles in reputable journals. Training and workshops have consistently been shown to have a positive impact on the productivity of academic staff and researchers. If academic staff are trained in writing and publishing research articles, it will go a long way to improve the contribution of African research to reputable journals. Hence, the focus of this study is to evaluate the workshop conducted on writing and publishing academic papers in highly reputable journals for academic staff in tertiary institutions. The study’s population consists of academic staff in tertiary institutions in Delta State, Nigeria. The sample comprised 59 academic staff who participated voluntarily in the workshop. Through a pre-questionnaire, a post-questionnaire, a participant satisfaction level questionnaire, and interviews, the four stages of the Kirkpatrick Model were used to assess the effectiveness of the workshop.High levels of participant satisfaction and notable advancements in academic writing, publication, and research exposure were observed as a result of the workshop. As they established online research profiles, identified predatory journals, and improved paper preparation, participants actively were able to apply their newly gained abilities. A 12-month post-workshop evaluation found remarkable results, including 18 participants publishing articles in journals with a Scopus index and many more creating profiles on Google Scholar, ResearchGate, and Academic.edu. The study highlights the significance of customised workshops in advancing research abilities and academic recognition by demonstrating a favourable association between customised workshops and increased research capabilities. Future evaluations can use the evaluation model as a useful framework, allowing for well-informed judgments about institutional and educational improvements.